Problematization strategy: experience report in the care process course in psyquiatric nursing - Claudinei José Gomes Campos; Fernanda Ribeiro Sobral (Universidade Federal do Ceará, 2013)
One aimed to present an experience report about the use of the problematization strategy in the teaching of the course Care Process in Psychiatric Nursing offered in the undergraduate nursing course at the Universidade Estadual de Campinas. One adopted as the methodology of the study a non-systematic observation and assessment of the theoretical productions developed by the students in the first semester of 2012. One believes that the change in the education of nurses must follow a new paradigm that redirects the relationship between professionals and the community, and that directs health actions in order to meet the real needs of the population. Despite the difficulties identified, one concluded that the use of this learning strategy can bring advantages and contributions to the teaching of psychiatric nursing.